Including gauge symmetry in the localization mechanism of massive vector fields (Publicaciones en Ciencias y Tecnología, 2014)
On the four-dimensional sector of an AdS5 warped geometry the standard electromagnetic interaction can be simulated by massive vector fields via the Ghoroku-Nakamura localization mechanism. We incorporate gauge symmetry to this theory by finding the required interaction terms between the vector bosons and the gravitational field of the scenario. The fourdimensional effective theory defined by a Maxwell term and a tower of Stueckelberg fields is obtained after expanding the vector fields on a massive eigenstates basis where the zero mode is uncoupled from the rest of the spectrum. The corrections generated by the massive gauge fields set to the electrostatic potential are also calculated.
Keywords: Brane worlds; vector fields localization; electrostatic potential